ANALISIS KEBUTUHAN BAHAN AJAR MATEMATIKA SISWA SMP KELAS VIII - Antonius KAP Simbolon (Yayasan Nusantara Hasana Berdikari, 2024)
In its implementation of the Merdeka curriculum to improve students' literacy and numeracy skills. The aim of this research is to determine the needs for mathematics teaching materials for class VIII SMP students in accordance with the independent curriculum. This research is a qualitative descriptive study. The subjects in this research were 30 students in class VIII of SMP N 2 Tanjung Morawa and 2 class VIII mathematics teachers. The sample in this research was obtained using purpose sampling technique. Data collection techniques include interview techniques and questionnaires. The data obtained was then analyzed. The data from the interviews is that students are not yet active in learning, there are limited mathematics teaching materials, the teaching materials used do not support the discovery of mathematical concepts, students are not yet able to understand abstract things in mathematics. The data from the student questionnaire are the learning sources used by students, including the internet 21.20%, textbooks from the government 71.27%, and textbooks from other sources 7.53%. Meanwhile, the questionnaire data on the need for teaching materials desired by students is 11.78% textbooks, 67.58% modules, 7.35% handouts, and 13.29% LKPD. The research results show that mathematics teaching materials are still very limited, students need teaching materials that are easy to understand and can be used independently. Based on the research results, it was concluded that it is necessary to develop realistic-based mathematics module teaching materials, with realistic-based mathematics module teaching materials that can guide students in discovering knowledge independently by relating the material to everyday life.